Kepemimpinan Kepala Sekolah Dalam Mengimplementasikan Program Sekolah Adiwiyata di SMP Negeri 2 Sukodono - Cahyani, Maharani Desita Eka; Kusuma, Risna Andara; Najwa, Fitri Adelia; Azahra, Zafira Nisa'; Wulandari, Ayu (CV Putra Publisher, 2024)
This study is the result of field research on Principal Leadership in Implementing the Adiwiyata School Program at SMP Negeri 2 Sukodono. This research centers on the discussion of the origin of SMP Negeri 2 Sukodono starting the Adiwiyata program, the role of school community in developing this Adiwiyata program, what programs have been successfully implemented by the Adiwiyata team from SMP Negeri 2 Sukodono. This research uses qualitative methods and literature. data obtained by researchers through observation, interviews, documentation, and collecting information from various sources such as books, journals, and research reports. Based on the research that has been done, it shows the conclusion that this program contributes significantly to the increase in the number of environmental awareness among students, teachers, and all school residents. In this program, the school principal has a very important role. However, there is a school Adiwiyata team that also has an important role in realizing the Adiwiyata program at SMP Negeri 2 Sukodono. In addition, the contribution of students and the entire school community is needed to make this program a success. Overall, this program has a positive impact on the school environment and its surroundings.